Pengaruh User-Generated Content sebagai Strategi Pemasaran Digital terhadap Keputusan Pembelian Konsumen pada UMKM Kuliner Warung Ketan Susu di Kota Tasikmalaya - Silvia Wijaya Rahmat; Getar Jagat Raya Rahmatul Annajam; Sayid Salim; Septi Sedyaning Hanurani; Wisnu Pramudya (International Forum of Researchers and Lecturers, 2026)
This study aims to examine the influence of User-Generated Content (UGC) as a digital marketing strategy on consumer purchase decisions, using Warung Ketan Susu, a culinary small and medium-sized enterprise (SME) in Tasikmalaya, as the research setting. A quantitative approach was employed by collecting data through interviews, observations, documentation, literature review, and questionnaires distributed to 100 consumers aged 18–30 years who actively use social media. The collected data were analyzed using simple linear regression. The findings reveal that User-Generated Content has a positive and significant effect on consumer purchase decisions, indicating that consumer-created content plays an important role in influencing purchasing behavior in the digital era. These findings suggest that culinary SMEs should integrate User-Generated Content into their digital marketing strategies to enhance consumer engagement and strengthen purchasing decisions. This study contributes to the digital marketing and SME management literature by providing empirical evidence on the effectiveness of User-Generated Content in supporting marketing performance within the culinary industry.